2007
DOI: 10.1128/jvi.02070-06
|View full text |Cite
|
Sign up to set email alerts
|

Basolateral Entry and Release of Crimean-Congo Hemorrhagic Fever Virus in Polarized MDCK-1 Cells

Abstract: Crimean-Congo hemorrhagic fever virus (CCHFV) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 40 publications
2
38
0
1
Order By: Relevance
“…Previously, we have shown that CCHFV does not directly target tight junctions, nor does it cause leakage in an in vitro model utilizing the Madin-Darby Canine Kidney (MDCK) epithelial cell line (12). We also found that infected moDCs activate endothelial cells, pointing to indirect targeting of the endothelium as a cause of vascular leakage (11).…”
Section: Fig 2 Activation Of Endothelial Cells Is Virus Dose Dependmentioning
confidence: 85%
See 1 more Smart Citation
“…Previously, we have shown that CCHFV does not directly target tight junctions, nor does it cause leakage in an in vitro model utilizing the Madin-Darby Canine Kidney (MDCK) epithelial cell line (12). We also found that infected moDCs activate endothelial cells, pointing to indirect targeting of the endothelium as a cause of vascular leakage (11).…”
Section: Fig 2 Activation Of Endothelial Cells Is Virus Dose Dependmentioning
confidence: 85%
“…In a previous article, we showed in an epithelial cell model of tight junctions that CCHFV does not disrupt barrier integrity, nor did infection result in internalization of critical tightjunction proteins (12). At the time, adherens junctions were not included in the study.…”
Section: Fig 2 Activation Of Endothelial Cells Is Virus Dose Dependmentioning
confidence: 99%
“…The virus enters and overcomes the epithelial barrier via the tick bite and enters the vascular system. The virus get inside the epithelial cells via clathrin-and cholesterol-dependent endocytosis [168], replicates in the cytoplasm and are newly formed virus are released from the cell side facing blood vessels [169]. The microtubules, a critical part of the cell cytoskeleton and migration machinery, are involved in the entering, replication and assembly of the virus in the cytoplasm, as well as in the viral exit of the host cell [170].…”
Section: Virusmentioning
confidence: 99%
“…In contrast, depleting Huh-7.5 cells of calcium had no effect on HCVpp or HCVcc infectivity, consistent with our observation that these cells do not form TJ-dependent paracellular barriers. Many viruses exhibit polarized routes of entry into primary and transformed epithelial cells, including vaccinia virus (37), VSV (8,20,40), human cytomegalovirus (18), Crimean-Congo hemorrhagic fever virus (12), coxsackievirus B, and adenovirus (14,15). Polarized entry can be mediated by several mechanisms, such as differential distribution of viral receptors on apical and basolateral surfaces, inaccessibility or inactivation of viral receptors, and postentry factors inhibiting viral replication.…”
Section: Vol 82 2008 Role Of Polarization In Hcv Entry 467mentioning
confidence: 99%